The establishment of Dar Al-Nadwa and its symbolism in Islamic history - محمد, ميلاد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The subject of the research deals with the study of the status of Dar al-Nadwah and the role it played in Mecca, at all economic, social, political and military levels, from its founding in the middle of the fifth century AD, by Qusayy bin Kilab until the early beginnings of Islam, with the conquest of Mecca by the Holy Prophet in the year 8 AH. When its pioneering role in leading important events ended as it was the headquarters of the meeting of the city’s senior tribal sheikhs. Hence, it was necessary to shed light on the direct and indirect influences that and the role played by Dar Al-Nadwa in Mecca, as the internal and external conditions of Mecca allowed it to become an advanced leadership center for Mecca at the regional level. In pre-Islamic times, it was the center for tribal meetings for consultation, in a way that ensured The city flourished and prevented disputes between its tribes. It was a center for concluding trade deals, resolving disputes, and making decisions about peace and war and all important issues. In the post-Islamic period, Dar al-Nadwa became the headquarters of a conspiracy against Islam in general, and the Messenger in particular, to prevent the Quraysh from losing its regional status and material wealth..